Students’ Interpersonal Relationship during the Adaptation in a New Gymnasium Class - Gailienė, Kristina (Pedagogika, 2015)
The study described in this article analyses the interpersonal relationships between the classmates in their first grade of gymnasium, as well as the factors influencing on these relations. Empirical study has confirmed the interpersonal relationships between the fist-grade gymnasium students to play an important role in their adjustment to the school community. The aim of the study: to determine the factors regulating the interpersonal relationships between the fist-grade gymnasium students during their adjustment in the school community. The object of the study: the interpersonal relationships between the fist-grade gymnasium students during their adjustment in the school community. Organisation and ethics of the study Both qualitative and quantitative surveys were carried out following the research ethics. The concept of the study was presented to the administration, teachers and students of the gymnasium involved in the study. Every participant received the explanation of the goals of the study, was guaranteed the anonymity and was ensured a free personal choice for participation. The research was conducted only on the approval of the administration of gymnasium and the student’s parents. The timing of surveys was adapted to the respondents’ comfort. The total of 482 first-grade gymnasium pupils and 377 teachers participated in the quantitative survey. Area covered by this research included the gymnasiums of Vilnius, Kaunas, Šiauliai, Klaipėda, Tauragė, Telšiai and Utena districts and Elektrėnai, Klaipėda, Mažeikiai, Panevėžys, Utena, Vilnius, Tauragė towns. 51 of the participant students coming from the Vilnius and Klaipėda city gymnasiums were also involved in the qualitative research. The survey was carried out by a researcher passively participating in the class meeting. The methods used Study of the scientific publications, questionnaire-based surveys, semi-structured essays. Data of the quantitative surveys was processed with SPSS (Statistical Package for the Social Sciences) 17.0 Windows software. For the statistical analysis we used the methods of descriptive statistics, the criteria of Mann-Whitney and Kruskal-Wallis, Spearman’s correlation and factor analysis. Statistical significance of the trait differences was evaluated by Pearsons Chi-Square (c2) test and Cronbach’s alpha coefficient. Analysis of data of the qualitative assay was based on the strategy by I. E. Seidman, inductive reasoning, content analysis and constant comparative method. The main results and conclusions The obtained data has shown that the interpersonal relationships in the newly formed class of gymnasium depend upon the following factors active during the adaptation process: perception of a membership in gymnasium‘s community, feelings of safety and respect, absence of bullying, number of earlier-formed friendships in the class. It’s worth noticing that the psychological climate in school as well as bullying affect the formation of new friendship bonds within a new class. The very basis of the adaptation process is the atmosphere of trust and collaboration. It facilitates the constructive problem-solving and encourages the personalities of the gymnasium fist-grades to unfold. We have also discovered that the familial structure of the students influences the formation of interpersonal relationships in their new class. Pupils placed into completely newly-formed classes, which exclude any former classmates from the 8th grade of school, have displayed a more favorable attitude towards spending time with their new classmates.